2015
DOI: 10.1002/2015jd023546
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary breakdown of intracloud lightning: Initiation altitude, propagation speed, pulse train characteristics, and step length estimation

Abstract: Using a low‐frequency lightning location system comprising 11 sites, we located preliminary breakdown (PB) processes in 662 intracloud (IC) lightning flashes during the summer of 2013 in Osaka area of Japan. On the basis of three‐dimensional location results, we studied initiation altitude and upward propagation speed of PB processes. PB in most IC flashes has an initiation altitude that ranges from 5 to 10 km with an average of 7.8 km. Vertical speed ranges from 0.5 to 17.8 × 105 m/s with an average of 4.0 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
82
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 25 publications
17
82
3
Order By: Relevance
“…(E‐change waveforms of the three downward +IC flashes analyzed in section are provided in Figures S9–S11.) This is in fact an expected result according to Wu et al (), which showed that the PB of IC flashes initiating at higher altitudes generally produced less frequent PB pulses with smaller amplitudes and smaller pulse widths. Similar results have also been reported by Proctor ().…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…(E‐change waveforms of the three downward +IC flashes analyzed in section are provided in Figures S9–S11.) This is in fact an expected result according to Wu et al (), which showed that the PB of IC flashes initiating at higher altitudes generally produced less frequent PB pulses with smaller amplitudes and smaller pulse widths. Similar results have also been reported by Proctor ().…”
Section: Discussionsupporting
confidence: 84%
“…Proctor () compared lightning flashes with low origins (1 to 7.4 km) and those with high origins (7.4 to 12 km) and found that channel extension speed was generally lower for high origin flashes. Wu et al () analyzed initial negative leaders in 662 IC flashes and demonstrated that the upward speed of initial negative leaders decreased as the initiation altitude increased. These results made us speculate that, if the initiation altitude is high enough, the initial negative leader of IC flashes would not even develop upward, and results of the current study confirm this speculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOLT is an LF sensor network that can be used to locate both IC and CG discharges in three dimensions. Each LF sensor detects electromagnetic wave radiations in the LF band associated with lightning discharges [ Ushio et al ., ; Wu et al ., , , ; Yoshida et al ., ]. After the identification of the pulse peaks of the LF records, the pulse peaks are located in three dimensions by using the time of arrival technique.…”
Section: Instrumentationmentioning
confidence: 99%
“…The range normalization was based on the 1/ r range dependence, where r was the average horizontal distance of the central station to all locations of the flash. Out of totally 2155 flashes, the number of relative errors ≥ 0.2 between the maximum (minimum) horizontal distance of the central station to all locations of each flash and r was 8 (2); note that most of PB heights were found below 10 km by Wu et al [], therefore below this height, the 2‐D location accuracy was estimated to be better than 2 km within areas of all four thunderstorms. So it could not affect the analysis results of PBA or RSA by r we took.…”
Section: Instrumentation and Methodologymentioning
confidence: 99%